KEPEKAAN HUMOR DENGAN DEPRESI PADA REMAJA DITINJAU DARI JENIS KELAMIN - Fitriani, Ayu; Hidayah, Nurul (Universitas Ahmad Dahlan, 2012)
This study aimed to identify the relationship between sense of humorsand depression in adolescents in terms of gender. The subjects of this studywere students of SMA Negeri 1 Sewon, Bantul, Yogyakarta class X andXI. The data collection tools of this study used the Beck Depression Inventory(BDI) and the Sense of Humor Scale Version-B, and used the analysiscovariance method to analyze the data. The results of this study showedsignificant differences in depression among female subjects and male subjects with a value of F = 6.905 and p = 0.010 (p <0.05) by controlling the sense of humor variable. The average level of female depression (7.284) was higher than male subjects (6.196). This result will be discussed further in this paper.